A Pilot Study of Music Teacher Identity: Towards an Eight-Stage Career Trajectory Model - Áron Pető; Judit Váradi (Harmonia: Journal of Arts Research and Education, 2026)
Music educators often navigate a dual professional identity shaped simultaneously by artistic and pedagogical roles. This exploratory pilot study examines the relationship between professional identity and career stages among Hungarian music teachers. While existing career models often assume linear progression, less attention has been given to how professional identity evolves across these stages in music education. This study proposes an eight-stage career trajectory model based on established life-course frameworks. Given the exploratory nature of the study and the limited sample size, the proposed model should be interpreted as a preliminary heuristic framework rather than a fully validated career model. Composite indices were created to measure teacher identity and integrated musician–teacher identity. The results indicate that the “active development” stage is dominant across different levels of professional experience, suggesting that career progression does not follow a strictly linear pattern. Furthermore, both identity dimensions showed only minor differences across career stages, indicating a relatively stable professional self-concept. Although the relationship between career stages and professional identity was one of the central aims of this study, the findings should be interpreted as exploratory rather than conclusive. Due to the small sample size and the cross-sectional design, the results provide only preliminary indications of how professional identity may be maintained, negotiated, or challenged across different career stages. Future longitudinal research is needed to examine these developmental patterns more systematically. These findings support a non-linear interpretation of career development and highlight the importance of integrating artistic and pedagogical identities in music teacher education.